Nonlinear dose–response relationship between dietary inflammatory index and risk of depression: a systematic review and meta-analysis - Yu, Lirong; Bian, Lingzi; Ren, Liping; Wei, Wei; Zhang, Huijie; Miao, Maoyun (Frontiers in Nutrition, 2025)
BackgroundDepression is a prevalent mental health disorders that impose a significant global health burden. Emerging evidence suggests that diet plays a critical role in mental health, primarily through its impact on inflammation. The Dietary Inflammatory Index (DII) is a validated tool designed to assess the inflammatory potential of an individual’s diet.ObjectiveTo systematically evaluate the association between DII and the risk of depression.MethodsA comprehensive search was conducted in PubMed, Cochrane Library, Embase, and Web of Science from inception to August 9, 2025. Two independent reviewers screened the studies, extracted data, and assessed methodological quality. A meta-analysis was performed to evaluate the association between DII and depression (the main outcome). The dose–response relationship between DII and depression was further analyzed using generalized least squares estimation and restricted cubic spline models in Stata 18.0.ResultsA total of 43 studies were included. The meta-analysis revealed that higher DII scores were associated with an increased risk of depression (OR = 1.53; 95% CI: 1.42 to 1.66; I2 = 81.5%). Subgroup analyses stratified by study design, gender, age, region, dietary assessment methods, depression assessment tools, and body mass index (BMI) consistently showed a positive association between higher DII and depression risk. Dose–response analysis indicated a nonlinear relationship (p = 0.0019): no significant association was observed for DII scores below 0, whereas the risk increased progressively for scores above 0. Exploratory analyses of a smaller subset of studies suggested a similar trend for anxiety, but this finding should be interpreted with caution.ConclusionHigher DII scores are associated with an increased risk of depression. These results highlight the potential benefits of reducing pro-inflammatory dietary components and encouraging anti-inflammatory eating patterns to support mental health, particularly in the prevention of depression.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023433767, identifier (CRD42023433767).